German newspaper data - die Welt and the Süddeutsche Zeitung - Rosengren, Inger (Lund University, 1987)
The data-file include running text from a representative sample of two German newspapers, Die Welt and Süddeutsche Zeitung, during the period 1 November 1966 to 30 October 1967.

Datafilen innehåller löpande text från ett representativt urval av två tyska tidningar, Die Welt och Süddeutsche Zeitung, under perioden 1 november 1966 till 30 oktober 1967.
Tyska tidningsdata - die Welt och Süddeutsche Zeitung
Keywords: Media; Media; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik